Biologically guided isolation and ADMET profile of new factor Xa inhibitors from Glycyrrhiza glabra roots using in vitro and in silico approaches. Issue 17 (9th March 2021) - Ibrahim, Reham S.; Mahrous, Rahma S. R.; Abu EL-Khair, Rasha M.; Ross, Samir A.; Omar, Abdallah A.; Fathy, Hoda M.
Abstract : Biologically guided isolation of new factor Xa inhibitors from Glycyrrhiza glabra roots. Abstract : Selective factor Xa inhibitors effectively block coagulation cascade with a broader therapeutic window than multitargeted anticoagulants. They have evolved as a crucial part of prevention and treatment of thromboembolic diseases and in therapeutic protocols involved in many clinical trials in coronavirus disease 2019 (COVID-19) patients. Biologically-guided isolation of specific FXa inhibitors from licorice ( Glycyrrhiza glabra ) root extract furnished ten flavonoids. By detailed analysis of their 1 H, 13 C NMR and MS data, the structures of these flavonoids were established as 7, 4′-dihydroxyflavone (1 ), formononetin (2 ), 3- R -glabridin (3 ), isoliquiritigenin (4 ), liquiritin (5 ), naringenin 5- O -glucoside (6 ), 3, 3′, 4, 4′-tetrahydroxy-2-methoxychalcone (7 ), liquiritinapioside (8 ) and the two isomers isoliquiritigenin-4′- O -β-d -apiosylglucoside (9 ) and isoliquiritigenin-4- O -β-d -apiosylglucoside (10 ). All the isolated compounds were assessed for their FXa inhibitory activity using in vitro chromogenic assay for the first time. Liquirtin (5 ) showed the most potent inhibitory effects with an IC50 of 5.15 μM. The QikProp module was implemented to perform ADMET predictions for the screened compounds.